Understanding Work in Schools: The Foundations of Teaching and Learning - McGrath-Champ, S.; Wilson, R.; Stacey, M.; Fitzgerald, Scott (NSW Teachers Federation, 2018)
Despite new and encroaching requirements relating to administration and accountability, teachers in schools retain their primary focus on matters directly related to working with students in teaching and learning. This accounts for the bulk of the daily work that they do. Yet there is also evidence that many teachers are struggling to preserve this student focus in the face of the new work activities that impose additional hours, work demands and personal burdens upon them. All Teachers, Head Teachers, Assistant Principals, Deputy Principals, Principals and Consultants highly value tasks which are perceived to be directly related to their teaching and to students’ learning, identifying planning and teaching lessons; meeting students’ learning needs; and communicating with students about their learning, lives and wellbeing as some of their most important work. However, they do not value administrative work which is impinging on this core focus, and is experienced as time consuming, cumbersome and concerned with compliance. This includes work associated with accreditation requirements; the collection, analysis and reporting of data; and compliance with state policies. There has been significant growth in overall hours, with 87 percent of survey respondents reporting an increase over the past five years since the implementation of devolved schooling through the Local Schools, Local Decisions policy. Classroom teachers most commonly report working upwards of 50 hours per week, which places teachers’ work in the category of ‘very long’ working hours.